Cost‐effectiveness of pancreas surveillance: The CDKN2A‐p16‐Leiden cohort. Issue 2 (13th February 2023) - Ibrahim, Isaura S.; Vasen, Hans F. A.; Wasser, Martin N. J. M.; Feshtali, Shirin; Bonsing, Bert A.; Morreau, Hans; Inderson, Akin; de Vos tot Nederveen Cappel, Wouter H.; van den Hout, Wilbert B.
Abstract: Background: CDKN2A ‐p16‐ Leiden mutation carriers have a high lifetime risk of developing pancreatic ductal adenocarcinoma (PDAC), with very poor survival. Surveillance may improve prognosis. Objective: To assess the cost‐effectiveness of surveillance, as compared to no surveillance. Methods: In 2000, a surveillance program was initiated at Leiden University Medical Center with annual MRI and optional endoscopic ultrasound. Data were collected on the resection rate of screen‐detected tumors and on survival. The Kaplan–Meier method and a parametric cure model were used to analyze and compare survival. Based on the surveillance and survival data from the screening program, a state‐transition model was constructed to estimate lifelong outcomes. Results: A total of 347 mutation carriers participated in the surveillance program. PDAC was detected in 31 patients (8.9%) and the tumor could be resected in 22 patients (71.0%). Long‐term cure among patients with resected PDAC was estimated at 47.1% ( p  < 0.001). The surveillance program was estimated to reduce mortality from PDAC by 12.1% and increase average life expectancy by 2.10 years. Lifelong costs increased by €13, 900 per patient, with a cost‐utility ratio of €14, 000 per quality‐adjusted life year gained. For annual surveillance to have an acceptable cost‐effectiveness in other settings, lifetime PDAC risk needs to be 10% or higher. Conclusion: The tumor could be resected in most patients with a screen‐detected PDAC. These patients had considerably better survival and as a result annual surveillance was found to be cost‐effective. Abstract :